Online Music Theory in Music Theory Online - Nicole Biamonte (Zeitschrift der Gesellschaft für Musiktheorie)
This essay surveys existing and potential approaches to publishing music theory and analysis in an online format. A brief consideration of the advantages and disadvantages of electronic journals is followed by an exploration of the different types of multimedia examples as used in the open-access journal Music Theory Online.